Effects of nozzle hole size and rail pressure on diesel spray and mixture characteristics under similar injection rate profile – experimental, computational and analytical studies under non-evaporating spray condition. (February 2022) - Safiullah,; Nishida, Keiya; Ogata, Youichi; Oda, Tetsuya; Ohsawa, Katsuyuki
In the present work, effects of nozzle hole size and rail pressure under non-evaporating spray condition are demonstrated. Three single hole injectors with the bore size of 0.101, 0.122, and 0.133 mm are experimented with injection pressures of 140, 45, and 38 MPa respectively to achieve similar injection rate profile. Diesel spray experiments implement Diffused Backlight Illumination Technique where diffused background is obtained for the High Speed Video camera imaging. Experimental results are then validated with computational and analytical studies. The CFD simulation requires the injection rate profile and spray cone angle as a primary input; thus, based on the High Speed Video Camera start of injection frame the 5 kHz Butterworth low-pass frequency filter is applied to the injection rate raw data. While, the spray cone angle is predicted using a simple model obtained from the relationship between the injection velocity, fluctuating velocity at the nozzle exit and total pressure loss factor of the injector. The experimental spray tip penetration of all three injectors is almost identical as the similar injection rate profile is adopted. Although, the mixture characteristics are better for 0.101 mm hole diameter since the smaller hole diameter with highest injection pressure depicts larger spray angle and better atomization. The computational study agrees with experiments qualitatively; however, the quantitative and qualitative agreements are seen in the analytical study.